Вплив чинників макросередовища на політико-ідеологічну ідентифікацію молоді - Агаларова, Карина Адільївна (Національний технічний університет "Харківський політехнічний інститут", 2017)
Стаття присвячена вивченню впливу чинників макросередовища політико-ідеологічної ідентифікації молоді. До чинників макросередовища належать: характеристики історичної епохи, конкретного суспільства, його політичної культури, національних і міжнаціональних відносин, державного устрою, класів та інших соціальних груп, до яких належить індивід. В статті доведено значна роль яку відіграють ці чинники у формуванні суб'єктних характеристик молоді. Також, у статті зроблено висновок про те, що сучасних умов політико-ідеологічні ідентифікації студентської молоді не отримують свого діяльнісного розгортання, не перетворюються на важливий повсякденний чинник її соціальної та політичної суб'єктності. За сучасних умов політико-ідеологічні ідентифікації студентської молоді не отримують свого діяльнісного розгортання, не перетворюються на важливий повсякденний чинник її соціальної та політичної суб'єктності, що зумовлюється як не розвинутістю української традиції практичної реалізації демократії (власне як простору боротьби ідеологій), так і тим, що політико-ідеологічні ідентичності вимушені боротися за "увагу" та діяльнісну реалізацію, зокрема з такими ідентичностями, як громадянська, етнічна, регіональна тощо.

The article is devoted to the study of the influence of the conditions of the macro environment on the formation of the politico-ideological identity of modern students. The formation of the political and ideological identity of modern students takes place under the influence of many factors, that is, the conditions that determine its content and specifics. These include the micro-and macro environment, lifestyle and individual characteristics of a person, the level of development of mass consciousness and other objective and subjective factors. Depending on the stage of political socialization, certain factors in the formation of a politico-ideological identity have a different degree of influence on the consciousness and behavior of the individual. To the conditions or factors, macroenvironments include: the characteristics of a historical epoch, a particular society, its political culture, national and interethnic relations, the state structure, classes and other social groups to which the individual belongs. The article proves the significant role of macro environment factors in the formation of subject characteristics of young people. It was also concluded that in modern conditions, the political and ideological identifications of student youth do not receive their developmental activity, they do not turn into an important everyday factor of its social and political subjectness, which is caused both by the undeveloped Ukrainian tradition of practical realization of democracy and by the fact that political-ideological identities must fight for "attention" and activity-oriented implementation, in particular, with such identities as civil, ethnic and regional. This is also explained by the fact that political and ideological identities are more closely related to language, regional, status, in other words, ascriptive criteria rather than achieved. Ukrainian practice of awareness and realization of identities is based primarily on aspiring criteria (which contradicts the very phenomenon of political-ideological complexes, but gives the right to analyze them exactly as identity).
Influence of macressed factors on political and ideological identification of youth
Keywords: політико-ідеологічна ідентичність; політична соціалізація; політична суб'єктність; студентська молодь; political and ideological identity; political socialization; political subjectivity